PID Parameters Improvement for AGC in Three Parallel-Connected Power Systems - Mushtaq, Najeeb; Ramdan, Razali; K. G., Mohammed; Hamdan, Daniyal; Ali, M. Humada (Universiti Malaysia Pahang, 2016)

(untitled)
In this research, the automatic generation control (AGC) of three parallel-connected power plants is utilized to tune the proportional-integral-derivative (PID) controller using Multistart algorithm (MS). The AGC loop is used to minimize the frequency deviation and control the power exchange in order to maintain them at their scheduled values due to the changes of the step-load disturbance. The optimal parameters of the PID scheme optimized by the proposed MS algorithm are compared with that one’s obtained by GA algorithm, and the proposed method has proven that its performance is more efficient and improved as well. Integral Square Error (ISE) is considered as an objective function for both algorithms to determine its performance index value for the same parallel-connected power system. From combination sets MS_PID_ISE and GA_PID_ISE; the settling time, maximum deviation and peak time are analyzed and compared in the time domain. Based on the simulated results, MS_ISE has better settling time, lesser peak time, and lower maximum deviation as compared with GA_ISE. Both of MS and GA algorithms are coded using MATLAB software.